2013
DOI: 10.1038/ncomms3071
|View full text |Cite
|
Sign up to set email alerts
|

Ground tit genome reveals avian adaptation to living at high altitudes in the Tibetan plateau

Abstract: The ground tit (Parus humilis) is endemic to the Tibetan plateau. It is a member of family Paridae but it was long thought to be related to the ground jays because of their morphological similarities. Here we present the ground tit's genome and re-sequence two tits and one ground jay, to clarify this controversially taxonomic status and uncover its genetic adaptations to the Tibetan plateau. Our results show that ground tit groups with two tits and it diverges from them between 7.7 and 9.9 Mya. Compared with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
214
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(234 citation statements)
references
References 49 publications
18
214
2
Order By: Relevance
“…Recently, more insight into adaptation to high-elevation habitats of QTP endemics resulted from a comparative genomic study: for the Tibetan Ground Tit (Pseudopodoces humilis), Qu et al (2013) demonstrated positive selection on genes linked with energy metabolism and skeletal development both associated with adaptations to a grounddwelling life and extreme environmental conditions at high elevations. What has remained enigmatic so far is whether these endemic QTP species never diversified to a notable degree during long-term isolate evolution or whether they represent relic lineages of a formerly more diverse clade.…”
Section: Early Colonisations Of the Central Qtp Alpine Plateau Habitatsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, more insight into adaptation to high-elevation habitats of QTP endemics resulted from a comparative genomic study: for the Tibetan Ground Tit (Pseudopodoces humilis), Qu et al (2013) demonstrated positive selection on genes linked with energy metabolism and skeletal development both associated with adaptations to a grounddwelling life and extreme environmental conditions at high elevations. What has remained enigmatic so far is whether these endemic QTP species never diversified to a notable degree during long-term isolate evolution or whether they represent relic lineages of a formerly more diverse clade.…”
Section: Early Colonisations Of the Central Qtp Alpine Plateau Habitatsmentioning
confidence: 99%
“…The remarkably high species richness of these mountain forests strongly contrasts with low species diversity on the central QTP itself. However, some of the cold-adapted high alpine endemics of the plateau itself have apparently evolved from rather ancient lineage splits and underwent long-term adaptation to extreme conditions (Qu et al 2013). In fact, there is evidence from the fossil record and from reconstructed biogeographic histories that the core QTP region was an evolutionary centre of origin (Deng et al 2011;Tseng et al 2013;Wang et al 2014)-emphatically termed a 'cradle of evolution' of cold-adapted mammals and forest-dwelling ground beetles (Erithra and Pterostichus; Schmidt et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…refs. 4 and 5), a topic of considerable interest in studies of endothermic birds and mammals (6)(7)(8)(9).…”
Section: Significancementioning
confidence: 99%
“…Some candidate genes involved in the HIF-1 signaling pathway have been shown to exhibit signatures of positive selection in Tibetans, yak, ground tit, Tibetan mastiff, and schizothoracine fish living in the Tibetan Plateau (Beall et al, 2010;Bigham et al, 2010;Storz, 2010;Qiu et al, 2012;Qu et al, 2013;Guan et al, 2014;Li et al, 2014). EPAS1 (HIF-2α), EGLN1, and PPARA in Tibetans, ADAM17 and Arg2 in yak, SRF, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al, 2013;Qu et al, 2013;Li et al, 2014). EGLN1 (1egl 9 homolog 1), PPARA (peroxisome proliferator-activated receptor-a genes) and EPAS1, also known as HIF2α (endothelial PAS domain 1) were significantly associated with hypoxia adaptation (Beall et al, 2010;Bigham et al, 2010;Simonson et al, 2010;Storz, 2010;Yi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%